Design optimization of steel–concrete hybrid wind turbine tower based on improved genetic algorithm. (28th March 2020) - Chen, Junling; Li, Jinwei; He, Xinheng
Summary: The steel–concrete hybrid wind turbine tower is characterized by the lower part of the traditional steel tubular tower replaced with the concrete segment. The lateral stiffness will be improved obviously, and then, the excessive vibration of the steel tower can be solved effectively. Based on the improved genetic algorithm, an optimization program is built to consider the influence of materials, labor, machinery, and transportation on the construction cost of a steel–concrete hybrid tower for a 2.0‐MW wind turbine with a hub height of 120 m, in which the initial height of the concrete segment is 32 m. During the optimization process, design requirements of relevant specifications and industry standards are used as the constraints. The optimization variables include the bottom and top diameters of the tower, the wall thickness of each segment, the height of the concrete segment, and the area of the prestressed steel strand. By comparing the results of construction cost and structural capacity before and after optimization, it can be found that the steel–concrete hybrid wind turbine tower after optimization has the better structural stiffness and lower construction cost. The proposed optimization program can meet the design requirements and significantly improve the economic performance of the tower.